Wnt5b‐associated exosomes promote cancer cell migration and proliferation. Issue 1 (23rd December 2016) - Harada, Takeshi; Yamamoto, Hideki; Kishida, Shosei; Kishida, Michiko; Awada, Chihiro; Takao, Toshifumi; Kikuchi, Akira
Abstract : Wnt5b is a member of the same family of proteins as Wnt5a, the overexpression of which is associated with cancer aggressiveness. Wnt5b is also suggested to be involved in cancer progression, however, details remain unclarified. We analyzed the biochemical properties of purified Wnt5b and the mode of secretion of Wnt5b by cancer cells. Wnt5b was glycosylated at three asparagine residues and lipidated at one serine residue, and these post‐translational modifications of Wnt5b were essential for secretion. Purified Wnt5b showed Dvl2 phosphorylation and Rac activation abilities to a similar extent as Wnt5a. In cultured‐cell conditioned medium, Wnt5b was detected in supernatant or precipitation fractions that were separated by centrifugation at 100 000 g . In PANC‐1 pancreatic cancer cells, 55% of secreted endogenous Wnt5b was associated with exosomes. Exosomes from wild‐type PANC‐1 cells, but not those from Wnt5b‐knockout PANC‐1 cells, activated Wnt5b signaling in CHO cells and stimulated migration and proliferation of A549 lung adenocarcinoma cells, suggesting that endogenous, Wnt5b‐associated exosomes are active. The exosomes were taken up by CHO cells and immunoelectron microscopy revealed that Wnt5b is indeed associated with exosomes. In Caco‐2 colon cancer cells, most Wnt5b was recovered in precipitation fractions when Wnt5b was ectopically expressed (Caco‐2/Wnt5b cells). Knockdown of TSG101, an exosome marker, decreased the secretion of Wnt5b‐associated exosomes from Caco‐2/Wnt5b cells and inhibited Wnt5b‐dependent cell proliferation. Exosomes secreted from Caco‐2/Wnt5b cells stimulated migration and proliferation of A549 cells. These results suggest that Wnt5b‐associated exosomes promote cancer cell migration and proliferation in a paracrine manner. Abstract : The secretory modes of Wnt5b varied among cancer cells and Wnt5b‐associated exosomes promote cancer cells migration and proliferation in a paracrine manner.